2016
DOI: 10.4252/wjsc.v8.i2.32
|View full text |Cite
|
Sign up to set email alerts
|

Generation of diverse neural cell types through direct conversion

Abstract: A characteristic of neurological disorders is the loss of critical populations of cells that the body is unable to replace, thus there has been much interest in identifying

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 158 publications
(189 reference statements)
0
7
0
1
Order By: Relevance
“…Transcription factors NFIa, NFIb and Ptbp1 indicated an astrocytic cell type. 11 , 34 - 36 The NFI family played important roles in the development of the central nervous system. 37 , 38 The study by Deneen et al indicated that NFIa was important in the transition from neurogenesis to gliogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors NFIa, NFIb and Ptbp1 indicated an astrocytic cell type. 11 , 34 - 36 The NFI family played important roles in the development of the central nervous system. 37 , 38 The study by Deneen et al indicated that NFIa was important in the transition from neurogenesis to gliogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…As in the pancreas and heart, iPSCs, embryonic stem cells (ESCs), and adult stem cells (i.e., mesenchymal stem cells) can differentiate into neurons in vitro ; however, the drawbacks of stem cell–based therapy include its potential tumorigenicity, the difficulty of generating diverse neuronal cell types, and the lack of full functionality in the induced neurons (Huang et al, 2015; Petersen et al, 2016). The direct conversion of glia/astrocytes to neuron-like cells in situ offers an alternative and promising strategy.…”
Section: Regeneration In Non-mammalian Vertebrates and Other Mammamentioning
confidence: 99%
“…By using pharmacologic and genetic methods, investigators determined that zinc-dependent HDACs are required for liver regeneration (Huang et al, 2013) and that overexpressing SIRT1 (a Class III HDAC) also suppressed hepatocyte proliferation by impairing farnesoid X receptor activity (Garcia-Rodriguez et al, 2014). Similarly, it has been thoroughly reviewed that epigenetic factors regulate the development and regeneration of pancreas (Avrahami et al, 2012; Migliorini et al, 2014), heart (Quaife-Ryan et al, 2016), and CNS (Arlotta et al, 2014; Petersen et al, 2016). …”
Section: Differences Between Hc Regeneration and Hc Developmentmentioning
confidence: 99%
“…der Schizophrenie und bipolaren Störung von Bedeutung sein könnten. Hinzu kommt, dass die Zahl an neuronalen Zellen durch die geringe verfügbare Menge an Patientenmaterial als auch durch die post-mitotische Natur von Neuronen beschränkt ist (58).…”
Section: Original Articleunclassified